Inovasi Pelayanan Publik Berbasis Digital dalam Meningkatkan Efektivitas Pelayanan Pemerintah kepada Masyarakat: Digital-Based Public Service Innovation in Increasing the Effectiveness of Government Services to the Community - Nur Mutmainna (Program Studi Manajemen Keuangan Sektor Publik, Politeknik Wahdah Islamiyah Makassar, 2025)
This study analyzes the role of digital-based public service innovations in improving the effectiveness of public services. Various government institutions in Indonesia have begun implementing digital transformation through online service platforms, mobile applications, and integrated information systems. These innovations are expected to reduce bureaucratic complexity, shorten service time, and increase transparency. Using qualitative literature analysis, the study finds that digital innovation significantly enhances accessibility, service quality, and public satisfaction. However, challenges remain, such as digital literacy gaps, infrastructure limitations, and system integration issues. Strengthening collaboration, improving digital competence, and ensuring stable technological infrastructure are essential to optimizing public service effectiveness.